Complete guide to respiratory care in athletes (Routledge, 2020)
Complete Guide to Respiratory Care in Athletes introduces the respiratory system and its function during exercise. It considers the main respiratory conditions affecting athletes and delivers practical advice for the management of respiratory issues in athletic populations.